If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -4 = -13 Reorder the terms: -4 + x = -13 Solving -4 + x = -13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = -13 + 4 Combine like terms: -4 + 4 = 0 0 + x = -13 + 4 x = -13 + 4 Combine like terms: -13 + 4 = -9 x = -9 Simplifying x = -9
| 16x^2+y^2-16y=0 | | r+10=15 | | 16x^2+y^2=16y | | -2+x=26 | | 2.1=x-6.1 | | (12)(6)6=x | | 3p=18 | | -10x=70 | | -7x=-168 | | -10.1x=30.3 | | 100(84)=96x | | -10x-20=-190 | | 4x+10x=56 | | 12z=-8 | | -11=x+4 | | 3x^2y+6x^2y^2-144xy^3= | | x^2-3x=-8 | | x=4+-3y | | x^2-18+77= | | 4(2x+-1)=27+3(2x-5) | | x(x+3)=18 | | 38=25+2y | | 7p=6p^2-3 | | v^2-6v+15= | | 0=-16t^2+35t+8 | | 1-5x^2=-3x | | 3(q+4)-10q=2q+3 | | 2x+3x+5=5(2x-3) | | 4z-2(z+6)=7z+8 | | 5x^2-30x-80= | | 6y+2y=9-3y | | 2x-5x=5+4y |